PENGARUH TEMAN SEBAYA TERHADAP MINAT MELANJUTKAN STUDI KE PERGURUAN TINGGI PADA SISWA SMA - Nur Ika Zulfa; Sri Mega Heryaniningsih; Muhamad Ridho Putra; Merita Kurnia Putri (Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Tasikmalaya, 2018)
The purpose of this research is to describe peer's affect of interest to continue studying to college in high school students. This research used literature study method. Based in result of literature study can be concluded that peer can affect student's interest to continue studying to college,because one of factors that affect interest continue studying to college is external factors where one of them is peer. Peer is very affecting decision taken by someone for their future. If their peers more oriented to school (continue studying to college), then that student will interested to continue his study to college,vice versa.therefore peer can affect interest continue studying to college towards student.